2010
DOI: 10.1007/s10856-010-4000-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite scaffolds processed using a TBA-based freeze-gel casting/polymer sponge technique

Abstract: A novel freeze-gel casting/polymer sponge technique has been introduced to fabricate porous hydroxyapatite scaffolds with controlled "designer" pore structures and improved compressive strength for bone tissue engineering applications. Tertiary-butyl alcohol (TBA) was used as a solvent in this work. The merits of each production process, freeze casting, gel casting, and polymer sponge route were characterized by the sintered microstructure and mechanical strength. A reticulated structure with large pore size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Fu et al 42 proved that freeze-cast HA with lamellar ($25 lm wide) and cellular ($100 lm in diameter) architectures are able to support the proliferation of preosteoblastic cells (MC3T3-E1) in vitro. By investigating the two types of pore architectures, it was demonstrated that the scaffolds with cellular pores showed far better cell proliferation, differentiation, and migration, suggesting that larger pores (>50 lm) are [19,20,56,91,95,97,103]. Fig.…”
Section: Hybrid Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fu et al 42 proved that freeze-cast HA with lamellar ($25 lm wide) and cellular ($100 lm in diameter) architectures are able to support the proliferation of preosteoblastic cells (MC3T3-E1) in vitro. By investigating the two types of pore architectures, it was demonstrated that the scaffolds with cellular pores showed far better cell proliferation, differentiation, and migration, suggesting that larger pores (>50 lm) are [19,20,56,91,95,97,103]. Fig.…”
Section: Hybrid Compositesmentioning
confidence: 99%
“…2i). 56,[78][79][80][81][82] Modifying the freeze conditions is another alternative to control the microstructures of freeze-cast scaffolds. Munch et al 71 showed that patterning the freezing surface can manipulate the long-range ordering of ice lamellae by controlling the initial direction of nucleation.…”
Section: Microstructural Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…water), is directionally frozen in a mold, then sublimated to remove the frozen liquid phase and sintered to densify the porous ceramics [16]. Several research groups have developed varying techniques for freeze-casting biocompatible ceramics, such as HA, for potential tissue engineering applications [17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The methods include uniaxial compaction [198,199], isostatic pressing (cold or hot) [200][201][202][203][204][205][206], granulation [207,208], loose packing [209], slip casting [210][211][212][213], gel casting [188,189,[214][215][216][217][218][219], pressure mold forming [220], injection molding [221], polymer replication [222][223][224][225], extrusion [226][227][228], slurry dipping and spraying [229], as well as to form ceramic sheets from slurries tape casting [124,216,230,231] doctor blade [232] and colander methods might be employed [194][195][196][197]233]. A combination of several techniques is also possible [216,234]. Furthermore, some of these processes might be performed under the magnetic field, ...…”
Section: Forming and Shapingmentioning
confidence: 99%